1977
DOI: 10.1128/aac.11.4.698
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Carbenicillin, Ticarcillin, Cephalothin, Cefazolin, Cefamandole, Gentamicin, Tobramycin, and Amikacin in Human Serum and Interstitial Fluid

Abstract: The ability of eight antibiotics (carbenicillin, ticarcillin, cefamandole, cephalothin, cefazolin, gentamicin, tobramycin, and amikacin) to enter human interstitial fluid was evaluated by the skin window technique. All of the antibiotics tested, except cefazolin, which has the highest percentage of protein binding, diffused into the interstitial fluid quite well. This study confirms our previous observation on the effect of high-percentage protein binding on diffusion of a drug into the minimally inflamed extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
26
0
1

Year Published

1978
1978
1996
1996

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 9 publications
0
26
0
1
Order By: Relevance
“…However, such studies have yielded disparate results, as shown by reports of poor cefazolin extravascular penetration in one study (11,12) and of good penetration in other studies (1,4,5,7,8).…”
mentioning
confidence: 94%
“…However, such studies have yielded disparate results, as shown by reports of poor cefazolin extravascular penetration in one study (11,12) and of good penetration in other studies (1,4,5,7,8).…”
mentioning
confidence: 94%
“…The combination of high serum levels and a reduced rate of excretion provides a prolonged half-life with sustained serum levels, which are thought to be responsible for superior tissue penetration (4,5,16,24). Although the ability of cefazolin to enter osseous tissue has been evaluated with bioassay techniques (6,11,23,31,32,35), the information obtained fails to fully define the osseous pharmacokinetics. Additionally, the osseous levels determined by bioassay have an erratic relationship to simultaneously determined serum levels (6,23,26,29).…”
mentioning
confidence: 99%
“…Carbenicillin (CBPC) has been used clinically since the late 1960s, and its pharmacokinetics have been extensively studied both in humans (8,12,13,17,19,20) and in animals (1,9,16,21). However, it has been used as a mixture of two epimers (R-CBPC and S-CBPC) because of the chirality of a (carboxyphenylacetyl)amino group attached to the 6 position of a penicillanic acid.…”
mentioning
confidence: 99%